Erosion Characteristics of Teflon under Different Operating Conditions - Nuruzzaman, D. M.; Debnath, U. K.; Chowdhury, M. A.; M. M., Rahman; Roy, B. K.; Kowser, M. A.; Islam, M. M. (Walter de Gruyter GmbH, 2015)
The present study investigated the solid particle erosion characteristics of Teflon under different impingement angles (15–90°), impact velocities (30–50 m/s), erodent sizes (300–600 μm) and stand-off distances (15–25 mm) at ambient temperature. The Teflon showed ductile erosion behavior exhibited a peak erosion rate at a 30° impact angle. The design of experiments approach utilizing Taguchi’s orthogonal arrays was applied to test the specimens on a compressed air jet type erosion test rig. Erosion efficiency (η) values were 0.29–16.7%, which indicates micro-plugging, plastic deformation and microcutting action as dominating erosion mechanisms. The experimental results are closer to the theoretical model. An optimal parameter combination was determined, which leads to minimization of erosion rate. Analysis of variance (ANOVA) was performed on the measured data and signalto- noise (S/N) ratios. A mathematical correlation, consistent with the experimental observations, is proposed as a predictive equation for estimation of erosion rate of tested material. The morphology of erodent surfaces was examined by using scanning electron microscopy (SEM). Possible erosion mechanisms are discussed.